Contribuições para a análise do comportamento fluidodinâmico de um leito vibrofluidizado. - Daleffe, Roger Valeri (2005)
Vibro-fluidized beds with inert particles as fluidizing medium have been appearing as an innovative technique for drying of suspensions and pastes. Aiming to contribute for the comprehension of phenomena involved in such processes, an investigation of fluid dynamic behavior of a vibro-fluidized (and also of a fluidized) bed with inert particles was carried out in this work. Glycerol was employed to wet the inert particles and then simulate the presence of a liquid paste into the bed. The purpose of the present work is to obtain a detailed investigation of the effects of amplitude, frequency of vibration, dimensionless vibration number, degree of liquid saturation, and of the particle size and density on the fluid dynamic behavior of the bed. The research included also an experimental investigation on the effects of the particle size distribution on the dynamic of inert particles into the fluidized, vibrated and vibro-fluidized beds, with an evaluation of size segregation patterns. The experiments were divided into three groups: in the first one, preliminary fluid dynamics tests were carried out; in the second one, the fluid dynamic behavior of fluidized and vibro-fluidized beds was investigated, and in the last one, the effects of particle size distribution on the dynamics of fluidized, vibrated and vibro-fluidized beds were verified. The experimental apparatus used in the tests was a vibro-fluidized bed constituted of a glass chamber, with a 0.114 m diameter cylindrical section, thickness of 0.003 m and height of 0.50 m. Ballotini spherical glass beads (ρp =2,500 kg/m3), with mean diameters from 1.10x10-3 to 17.00x10-3 m, polypropylene spheroids (ρp = 935 kg/m3) with mean diameters of 2.60x10-3 and 3.67x10-3 m and elliptical cylinders of polystyrene (ρp = 1,050 kg/m3) with equivalent diameter (volumetric diameter) of 2.51x10-3 m, were used as inert particles. The bed was operated under dimensionless vibration numbers from 0.00 to 6.00, for amplitudes varying from 0.000 to 0.021 and frequencies of vibration from 0.00 and 18.20 Hz. Glycerol saturation degrees (defined as the ratio between volume of glycerol and volume of voids in the fixed bed) varied from 0.0000 and 0.0072. The glycerol was employed to simulate the presence of a liquid fed into the bed in a batch mode, since it practically does not evaporate under the conditions of present work. Identical values of dimensionless vibration numbers (Γ) were obtained using different combinations of amplitudes (A) and frequencies of vibration (f), aiming to verify the universality of such a parameter to describe vibration characteristics of a vibro-fluidized bed. Four types of size distribution models were used in the investigation of the effects of the particle size distribution on the dynamics of vibro-fluidized beds: binary, flat, Gaussian and a reference one, all of them with a mean Sauter diameter of 2.18x10-3 m. In the range of experimental conditions investigated, it was observed that the dimensionless vibration number does not fully characterize the fluid dynamic behavior of the vibrated systems. Some degree of particle agglomeration was always observed in the presence of glycerol, yielding to an irregular and poor fluidization. The use of vibration in such cases improved the particle circulation in the bed, thus reducing the agglomeration and minimizing the formation of channelling. When specific particle size distributions were adopted for fluidization, some size segregation pattern was observed in almost every case. In the fluidized bed, the smallest particles stayed at the top of the column, while in the vibrated one the largest particles tended to concentrate at the top. In a vibro-fluidized bed under short amplitude of vibration (0.003 m), some segregation was noted but in a less extent than that observed in the fluidized bed at similar conditions. At high amplitude of vibration (0.009 m), no size segregation was detected.